Kiai Azaim Ibrahimy's Thought on Happiness and Well-Being: The At-Tawazun Approach in Society 5.0 - Arifin, Samsul; Saputra, Rahmat (UIN Maulana Malik Ibrahim Malang, 2025)
In the face of Society 5.0 and rapid digitalization, younger generations are increasingly vulnerable to emotional imbalance, a diminished spiritual connection, and weakened social bonds. This study explores the thoughts of K.H.R. Ach. Azaim Ibrahimy on happiness and psychological well-being, as conveyed through the Majelis Dzikir Basmalah YouTube channel, and examines their alignment with Martin Seligman’s PERMA model. This study addresses a gap in existing research by integrating the spiritual teachings of Kiai Azaim Ibrahimy with Seligman’s PERMA model to explore well-being in Islamic boarding schools, a context largely overlooked in both Islamic and psychological literature. Its novelty lies in offering a holistic framework that combines local spiritual wisdom with positive psychology to respond to the mental health challenges of pesantren communities in the digital Society 5.0 era. Using a qualitative hermeneutic-ethnographic approach, the research reveals that Kiai Azaim’s teachings resonate with the five pillars of PERMA: gratitude as a source of positive emotion, spiritual engagement through religious devotion, harmonious interpersonal relationships, a meaningful life rooted in service, and a sense of accomplishment encompassing both worldly and spiritual success. The study further analyzes the implementation of the At-Tawazun counseling model in pesantren (Islamic boarding school) settings, which incorporates local wisdom through practices such as uswah hasanah (exemplary conduct), ta’zhim (reverence), khidmah (service), and riyadhah (spiritual discipline). These traditions foster spiritual, social, and psychological harmony within the pesantren environment. The findings underscore the strategic role of pesantren-based counseling as a contextual, holistic, and culturally grounded approach to enhancing mental well-being in the digital age. Consequently, pesantren emerge not only as spiritual institutions but also as vital centers for nurturing psychological resilience amid global change. Di tengah tantangan era Society 5.0 dan digitalisasi, generasi muda menghadapi ketidakseimbangan emosional yang kian kompleks. Ketergantungan pada teknologi, tekanan sosial media, serta melemahnya ikatan spiritual dan sosial berkontribusi terhadap menurunnya tingkat kebahagiaan dan kesejahteraan psikologis. Studi ini bertolak dari kegelisahan tersebut, dengan meneliti pemikiran Kiai Azaim Ibrahimy tentang kebahagiaan dan kesejahteraan jiwa yang disampaikan melalui kanal YouTube Majelis Dzikir Basmalah, dan mengaitkannya dengan model PERMA dari Martin Seligman. Melalui pendekatan kualitatif dengan metode hermeneutik-etnografis, penelitian ini menemukan bahwa ajaran Kiai Azaim selaras dengan lima dimensi PERMA: syukur sebagai sumber emosi positif, keterlibatan spiritual dalam ibadah, relasi sosial harmonis antar santri, makna hidup dalam bingkai pengabdian, serta pencapaian yang mencakup keberhasilan dunia dan akhirat. Penelitian ini juga menelaah praktik konseling At-Tawazun di pesantren yang mengintegrasikan kearifan lokal melalui metode uswah hasanah, ta’zhim, khidmah, dan riyadhah. Teknik-teknik ini terbukti efektif dalam menumbuhkan keseimbangan spiritual, sosial, dan psikologis di lingkungan pesantren. Temuan ini menegaskan pentingnya pengembangan pendekatan konseling berbasis pesantren sebagai model alternatif yang kontekstual, relevan, dan holistik untuk memperkuat ketahanan mental di era digital. Dengan demikian, pesantren tidak hanya berfungsi sebagai lembaga pendidikan spiritual, tetapi juga sebagai pusat penguatan kesejahteraan psikologis yang adaptif terhadap dinamika global.